Competitiveness Analysis of ASEAN Automotive Industry: A Comparison between Malaysia and Thailand (Journal of Science, Technology and Innovation Policy, 2021)
The automotive industry in ASEAN started thirty years under different automotive policies and approaches leasing to different performance among its country members. This paper focus on Porter’s five forces model analysis between Malaysia and Thailand since these two countries are made up the top three vehicles manufacturers in ASEAN. Thailand’s annual production exceeds two million vehicles per year compared to Malaysia around five hundred thousand vehicles. The automotive components and parts in Malaysia recorded trade deficit which import of automotive parts at RM 4 billion of values compared to exported parts only at RM2 billion. Previous study suggested Thailand successful automotive policy strategy which launched thirty years ago emphasized on dependent strategy on foreign investment whereas Malaysia focus its automotive development on its national car company Proton. After thirty years, the successful Thailand performance in the automotive industry has been viewed as saturated and dominated by Japanese and American manufacturers. On the contrary, the lack of performance in the automotive manufacturing and components industry in Malaysia has been seen as attractive for investors to invest in Malaysia. Furthermore the high car passenger density in Malaysia offers advantage for the manufacturer in this industry.
Keywords: Industry Analysis; Government Automotive Policy; Porter’s five Forces Analysis; Malaysian and Thailand Automotive Industry